Children living in Refugee Camps - Santos, Luisa Micaela Teixeira (2019)
According to the International Council of Nurses, nurses are a key factor in the health responses to these populations, especially in the area of mental health. Therefore, this study aims to study the vulnerability and protective factors in mental health of asylum seeking children living in a refugee camp. The study of these factors is essential for the construction of specific mental health promotion programs that can be implemented by specialist nurses. Methodology: A qualitative, exploratory and descriptive study carried out in the Refugee Camp of Kara Tepe, Island of Lesbos, Greece. Results: From the analysis of the data collected, the following factors of vulnerability in mental health in children seeking asylum emerged: Traumatic Experiences; Difficulty of Expression Emotions; Loss of Identity References; Feelings of Abandonment and Loneliness; Current Life Conditions in Refugee Camps; Lack of Prospects for the Future. As protective factors in mental health the following categories emerge: Hope and Resilience; Formal and Non-Formal Education; Safety and Security Environment.